Alternative Forms of Enhanced Boussinesq Equations with Improved Nonlinearity. (7th April 2013) - Fang, Kezhao; Liu, Zhongbo; Gui, Qinqin; Zou, Zhili; Yin, Jiwei
Abstract : We propose alternative forms of the Boussinesq equations which extend the equations of Madsen and Schäffer by introducing extra nonlinear terms during enhancement. Theoretical analysis shows that nonlinear characteristics are considerably improved. A numerical implementation of one-dimensional equations is described. Three tests involving strongly nonlinear evolution, namely, regular waves propagating over an elevated bar feature in a tank with an otherwise constant depth, wave group transformation over constant water depth, and nonlinear shoaling of unsteady waves over a sloping beach, are simulated by the model. The model is found to be effective.